2008
DOI: 10.1007/s10681-008-9860-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of partial resistance to coffee leaf rust (Hemileia vastatrix Berk & Br.) introgressed into the cultivated Coffea arabica L. from the diploid C. canephora species

Abstract: The objective of this study was to identify polymorphic molecular markers associated with partial resistance to coffee leaf rust, Hemileia vastarix. A segregating F 2 population derived from a cross between the susceptible Coffea arabica cv. Caturra and a C. canephora-introgressed Arabica line exhibiting high partial resistance was analyzed. Rust resistance measured as rust incidence (RI) and defoliation (DEF) was evaluated in field conditions in three consecutive years (2003)(2004)(2005). During the 2003 seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…However, no significant correlation among the molecular markers and the presence of lesions in coffee leaves infested by L. coffeella was detected. Herrera et al (2009) evaluated the Sat 225 and Sat 229 loci in a F 2 segregating population resulting from a cross between the susceptible C. arabica cultivar Caturra and the resistant female parental hybrid derived from the cross between C. arabica and C. canephora. These authors observed the occurrence of a variable amplification pattern during the evaluated years, which may be associated with the infestation pressure of the pathogen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no significant correlation among the molecular markers and the presence of lesions in coffee leaves infested by L. coffeella was detected. Herrera et al (2009) evaluated the Sat 225 and Sat 229 loci in a F 2 segregating population resulting from a cross between the susceptible C. arabica cultivar Caturra and the resistant female parental hybrid derived from the cross between C. arabica and C. canephora. These authors observed the occurrence of a variable amplification pattern during the evaluated years, which may be associated with the infestation pressure of the pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 28 EST-SSR primers (Pinto et al, 2007) and three more SSR loci, already characterized for coffee biotic stress (Herrera et al, 2009) (1) CA1, non embryogenic callus; LV5, pointer leaf -orthotropic branch without Bion -short; LV9, pointer leaf -plagiotropic branches without Bion -short; RT3, root without Bion; RT5, root with Bion; CL2, hypocotyl callus with and without Bion; FR1, flower bud no. 6, lead no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The progênies originated from clone 83 and clone 02 showed a wide spectrum levels from resistance to susceptibility. Horizontal resistance is commonly observed in C. canephora although it also occurs in some genotypes of C. arabica progenies of Híbrido de Timor (Eskes 1983;Eskes 2005;Herrera et al 2009;Romero et al 2010). Breeding programs to rust resistance have been nowadays looking for the quantitative reaction of the plant genotypes due to the vulnerability of the qualitative resistant cultivars to the emerging races of H. vastatrix.…”
Section: Discussionmentioning
confidence: 99%
“…The number of known markers and molecular information on coffee leaf rust-resistance genes are limited (Herrera et al 2009). To date, genetic maps saturated for C. arabica containing genes or QTLs controlling this trait have not been made available.…”
Section: Introductionmentioning
confidence: 99%